Interface enhancement mechanism of rolled Mg/Al clad plate with particle interface control - Xiaobao Ma; Peng Li; Tao Wang; Zhongkai Ren; Peng Chen; Jiang Ji (Journal of Magnesium and Alloys)
In this study, the cold-spraying process was utilized to deposit Al particles onto an Al slab, an Mg slab, and both Al and Mg slabs to form an ultra-thin interlayer, and then the clad slabs were rolled at 400 °C, developing three roll-bonding processes: the roll-bonding process with cold-sprayed Al powder on the Al slab (CS-Al), the roll-bonding process with cold-sprayed Al powder on the Mg slab (CS-Mg), and the roll-bonding process with cold-sprayed Al powder on both the Al slab and the Mg slab (CS-Both). The effects of three different cold-sprayed Al particle interlayer processes on the mechanical properties of rolled Mg/Al clad plates were investigated to improve the mechanical properties. The microstructure, texture evolution, intermetallic compound formation, mechanical properties, and mechanisms involved in the Mg/Al clad plate rolling were systematically investigated. The results showed that the pre-bonding between the particles and the substrates through cold-spraying had a significant impact on the bonding strength of the Mg/Al clad plates, and the CS-Both process can increase the average shear strength of the Mg/Al clad plates to 49.24 MPa at a medium reduction rate of 37.5 %, 2.5 times that of the conventional rolling process. The CS-Both process constructed more evident dual microscopic three-dimensional interfaces and promoted more thorough atomic diffusion at the interface through the double-sided cold-spraying process. Meanwhile, the dual cold-sprayed Al coatings on both the Mg slab and Al slab underwent dynamic recrystallization during rolling to form a homogeneous unit with no additional coating interfaces. Fine grain strengthening and dislocation strengthening were judged to be important mechanisms for improving the mechanical performance of the interfacial layer.